Assessment of green supply chain risk based on circular economy - Zhen-kun Yang; Jian Li (2010 IEEE 17Th International Conference on Industrial Engineering and Engineering Management, 2010)
Circular economy is the main direction of the development of world economy, and now it is the economy developing pattern of our country. This paper describes the operation of green supply chain, and re-assesses the risk system of green supply chain, and then use Fuzzy-AHP comprehensive evaluation model to make an assessment for the Green Supply Chain Risk to provide a reliable basis and assurance for the Supply chain selection and risk control of enterprise.